COD fractions - methods of measurement and use in wastewater treatment technology = Frakcje CHZT - metody pomiaru oraz zastosowanie w technologii oczyszczania ścieków - Myszograj, Sylwia; Płuciennik-Koropczuk, Ewelina; Jakubaszek, Anita; Świętek, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the results of studies concerning the designation of COD fraction in raw wastewater. The research was conducted in four municipal mechanical-biological sewage treatment plants and one industrial sewage treatment plant. The following fractions of COD were determined: non-biodegradable (inert) soluble SI, biodegradable soluble fraction SS, particulate slowly degradable XS and particulate non-biodegradable XI.
Keywords: COD fractions; raw wastewater; methods of measurement; frakcje ChZT; ścieki surowe; metody pomiaru